Isolamento, determinação estrutural e atividades biológicas de metabólitos dos fungos Phellinotus piptadeniae E Pisolithus tinctorius - Carmo, Gabriele do (2019)
Basidiomycete fungi are important living organisms that present several bioactive compounds, which have antimicrobial, antitumor, antioxidant, and anti-inflammatory potential. Several compounds and potentialities of this class of fungi are still unknown. Therefore, the objective of this work was to prepare fractions of Phellinotus piptadeniae and Pisolithus tinctorius, isolate and identify the secondary metabolites, and evaluate the antimicrobial activities of the fractions and compounds obtained. The antioxidant activity was just assessed for the fractions from P. piptadeniae species. The chemical investigation of P. piptadeniae led to the isolation of five compounds, two triterpenes (ergosterol peroxide (D1) and ergosterol (D2)), two long chain esters (pentadecanoic acid-2-hydroxy, ethyl ester (D6) and tetracosanoic-2-hydroxy, methyl ester (D11)), and a phenolic compound (derived from hispidin (D9)), which was not yet described. The ergosterol acetate (D2a) was obtained from an structural modification through the acetylation reaction of triterpene D2. The study of the Pisolithus tinctorius species drive to the isolation of two lanostane triterpenes (pisolactone (P180) and lanostane, 7,22-dien-3-ol, 24-methyl (P65)), where, P65 compound was identified as a novel metabolite in the literature. In addition, a long chain acid (5-hexadecenoic acid (P1)) and ceramide (P56), it was not in this species, were also identified. All fractions obtained from the species P. piptadeniae and P. tinctorius had antibacterial and antifungal actions. Whereas, against mycobacteria, only the hexanic and methanolic fractions of P. piptadeniae and the ethyl acetate fraction of P. tinctorius were effective at the concentrations tested. The triterpenes, acid derivatives and phenolic compound were active against bacteria (Gram-positive and Gram-negative), fungi and mycobacteria. The ethyl acetate and methanolic fractions of the P. piptadeniae species, when tested against their antioxidant capacity, showed promising results with IC50 because their values were close to the BHT standard.